Psychoanalysis by the Numbers: What Bearing Does Frequency of Sessions Have on the Education and Training of Child Psychoanalytic Candidates?. Issue 1 (31st December 2022) - Singer, Michael
ABSTRACT: In 2018, the IPA and the APsaA changed their training requirements for graduation for child and adolescent candidates. The modified standards permitted constituent societies and institutes who followed the traditional Eitington training model to offer their candidates the choice of treating one or more of their supervised cases at a frequency of 3 times per week, rather than the traditional four or five times per week. Controversy over the issue of frequency had preceded this change and has continued after the change. The author attempts to discuss all sides of the debate, addressing the benefits and the costs of each level of frequency. In the absence of good research on this question, the author asked experienced child analysts and some candidates to weigh in with their experiences and opinions. Some areas of consensus as well as areas of disagreement emerged.